Highways, Functions and Importancein the Republic of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The development of the transport communications and the improvement of their use one of the most pressing tasks in the development of the economy. The share of highways in the national freight traffic in the country shows that highways are one of the key factors in the development of the country's economy.